Primerjava pravnih ureditev finančnih trgov v državah bivše Jugoslavije - Kocjančič, Rok (Podjetje in delo, 2024)
The article examines the legal regulation of stock exchanges of six countries of the former Yugoslavia: Slovenia, Bosnia and Herzegovina, Croatia, Montenegro, North Macedonia, and Serbia. The discussion focuses on the factors which, at least in the initial stages of consideration on the possibility of listing, have a strong influence on the potential decision to list and the choice of market for listing. These factors are: market regulators, governance of the securities register, settlement procedure, listing of securities, market segmentation, and delisting of securities. Market regulators shape the legal environment of the market and oversee the implementation of the rules in practice, thus ensuring legal certainty. The functions of securities register and settlement of obligations between participants are performed by a single institution in each of the countries concerned. The regulation of the listing of a security on the stock market is strongly linked to market segmentation. A combination of the following two criteria is mostly used: the type of security and the profile of the issuing company, with varying emphasis on the profile of the company versus the type of security. All exchanges regulate the typical reasons for delisting, of which the most important for the majority of issuers is voluntary delisting following a delisting decision. Few stock exchanges regulate delisting in a detailed and systematic way.
Keywords: borza; borzni trg; delisting; listing; poravnava; pravila; register; regulacija; regulations; rules; segmentacija; segmentation; settlement; stock exchange; stock market; umik; uvrstitev